Management of Sustainable Development of the Fuel and Energy Complex of the Regional Economic System Based on Digital Technologies - Ekaterina A. Zemlyacheva (RUDN Journal of Economics)
The relevance of the scientific and practical problem solved in the article is due to the fact that the existing approach to managing the development of the fuel and energy complex in the regional economic systems of Russia, based on state regulation, does not fully ensure its sustainability, therefore it is advisable to activate the market mechanism. The purpose of the article is to develop an approach to corporate management of sustainable development of the fuel and energy complex of a regional economic system based on digital technologies. To do this, based on statistics for the regions of Russia in 2022, an econometric model for managing the sustainable development of the fuel and energy complex of the regional economic system based on digital technologies is compiled using the method of regression analysis. As a result, it was concluded that digital technologies largely determine the sustainability of the fuel and energy complex in Russian regional economic systems, but flexible use of these technologies is necessary, focusing on those that most and consistently support the sustainable development of the fuel and energy complex in the regions of Russia. For this purpose, an approach to corporate management of sustainable development of the fuel and energy complex of the regional economic system based on digital technologies has been developed. Features of the new approach are: 1) transition from public administration to corporate governance; 2) reliance on digital technologies in management; 3) flexible use of digital technologies in management, which involves the limited and careful use of controversial technologies (geographic information systems, Internet of things, cloud services and artificial intelligence) and the expansion of the use of key technologies that positively affect the sustainability of the fuel and energy complex in the regional economy of Russia: ERP systems, large data and digital platforms. The theoretical significance of the new scientific results obtained in the article and the author’s conclusions made is due to the fact that they outlined the range of priority digital technologies for the sustainable development of the fuel and energy complex, which included ERP systems, big data and digital platforms. The practical significance of the developed approach is that it will increase the flexibility and efficiency of managing the sustainable development of the fuel and energy complex of the regional economic system and most fully reveal the potential of this development in the regions of Russia by optimizing the use of digital technologies according to the author’s recommendations.